PENDAPATAN USAHA SAYURAN HIDROPONIK ANDRI FARM DI KELURAHAN HANGA-HANGA KABUPATEN BANGGAI - Ruslan A Zaenuddin; Fina Potabuga; Ambo Abd. Kadir Pakanyamong (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
Vegetables produced using hydroponic technology have better quality compared to conventional vegetables but the cost required is high. The goal to be achieved in this study is to find out how much cost and income as well as the feasibility of hydroponic vegetable business at Andri Farm. This research was carried out in the month of june until the month august 2022, using quantitative approaches and income analysis methods and R/C ratios to calculate revenue and like the business of Andri Farm. The results of the research obtained are the large costs incurred in Andri Farm's hydroponic vegetable business in a month amounting to Rp 21,717,292.15 and Andri Farm's hydroponic vegetable business income in a month amounting to Rp 10,497,707.85. Based on the cost of expenditure and income of Andri Farm's hydropinic vegetable business, the R/C result of > ratio was obtained, with a final result of 1.48, so that Andri Farm's hydroponic vegetable business is feasible to be developed